EDUCATION FINANCING AND TAXATION SYSTEM - Muhammad Bolot Iswanto (Proceeding International Seminar of Islamic Studies, 2021)
In the current era of globalization, Indonesians are required to be educated, meaning they are required to master various things and abilities. To be able to provide and improve abilities is to go to school or enter an educational institution. But unfortunately not all Indonesians can enjoy this education due to limited financial capacity. This is a serious problem in the development of the world of education in Indonesia. In order to fulfill the citizens' rights as mentioned above, the Central Government and Regional Governments are obliged to provide services and facilities and ensure the implementation of this education without any discrimination. The Central Government and Regional Governments are obliged to guarantee the availability of funds to provide education for every citizen, at least for citizens aged seven to fifteen years.One of the goals of the government of the Republic of Indonesia which is stated in the fourth paragraph of the Preamble of the 1945 Constitution, namely protecting the entire Indonesian nation and all Indonesian blood, advancing public welfare, educating the nation's life and participating in implementing world order based on independence, eternal peace and social justice (in bold and underlined by the author). The consequence that must be borne by the state by including the word